Chronic heart failure decreases cross-bridge kinetics in single skeletal muscle fibres from humans - Miller, Mark S (Blackwell Science Inc, 2010)
Skeletal muscle function is impaired in heart failure patients due, in part, to loss of myofibrillar protein content, in particular myosin. In the present study, we utilized small-amplitude sinusoidal analysis for the first time in single human skeletal muscle fibres to measure muscle mechanics, including cross-bridge kinetics, to determine if heart failure further impairs contractile performance by altering myofibrillar protein function. Patients with chronic heart failure (n = 9) and controls (n = 6) were recruited of similar age and physical activity to diminish the potentially confounding effects of ageing and muscle disuse. Patients showed decreased cross-bridge kinetics in myosin heavy chain (MHC) I and IIA fibres, partially due to increased myosin attachment time (t(on)). The increased t(on) compensated for myosin protein loss previously found in heart failure patients by increasing the fraction of the total cycle time myosin is bound to actin, resulting in a similar number of strongly bound cross-bridges in patients and controls. Accordingly, isometric tension did not differ between patients and controls in MHC I or IIA fibres. Patients also had decreased calcium sensitivity in MHC IIA fibres and alterations in the viscoelastic properties of the lattice structure of MHC I and IIA fibres. Collectively, these results show that heart failure alters skeletal muscle contraction at the level of the myosin–actin cross-bridge, leading to changes in muscle mechanics which could contribute to impaired muscle function. Additionally, we uncovered a unique kinetic property of MHC I fibres, a potential indication of two distinct populations of cross-bridges, which may have important physiological consequences.